Preparation of Hybrid Junction Light Emitting Device from Cadmium Sulphite Quantum dot/ poly-TPD Junction - Riyadh Mohammed , Hussein; A. Ibrahim , Omar (University of Thi-Qar Journal of Science, 2021)
Stratums of ITO/TPD:PMMA/CdS/Alq3/Al were used to make the hybrid nanoparticles light emitting diode (NPs-LED), which were created using the phase segregation method and the spin coating procedure. Light-generating NPs-LED hybrid device is composed of 3 stratums stacked in a certain order on an Indium tin oxide(ITO) substrate made of transparent conducting oxide. The first stratum was (N, N'-bis (3-methylphenyl)-N, N'-bis (phenyl) benzidine) (TPD) polymer, and polymethyl methacrylate (PMMA) polymer. Cadmium Sulphite (CdS) is the second stratum, while Tris (8-hydroxyquinolinato) aluminum (Alq3) is the last stratum, which is one of the materials used as electron injector stratums.Various bias voltages (28, 30, and 32V) were used to examine the electroluminescence (EL) of NPs-LEDs at room temperature, depending on the CIE 1931 color spaces, `light was created at 32V, whereas blue light was generated at 28V. The transmission between sub levels in the energy gap of CdS NPs (surface state). Voltages are controlling the current change, and the knee voltage is 6.6 V, as seen by the current – voltage (I-V) distinctive. EL spectrum demonstrates a broadband emission spanning 300 nm to 700 nm. Finally, it is discovered that the correlated color temperature (CCT) is about (7450 to 11820k).